PENGARUH REGULASI DIRI DAN KARAKTER KERJA KERAS TERHADAP PRESTASI AKADEMIK MAHASISWA PEKERJA PARUH WAKTU - Syarifah Naila Kamila; Monry Fraick Nicky Gillian Ratumbuysang; Mahmudah Hasanah; Syaripudin Bahar (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to determine the effect of self-regulation and hard work character on academic achievement in students of the Faculty of Teacher Training and Education, Lambung Mangkurat University class of 2021. The research method used in this research is descriptive-quantitative method, using data collection techniques through questionnaires. The population in this study were students of FKIP Lambung Mangkurat University class of 2021 who worked part-time. The sampling technique in this study used non-random sampling, namely purposive sampling, with a sample of 100 respondents. The analytical tool used is Structural Equation Modeling (SEM) using SmartPLS version 4.0 software.Â The results of this study indicate that from the partial calculation results for the self-regulation variable, the p-value is 0.830> 0.05 and the t-statistic value is 0.214 < 1.96 with an original sample value of 0.026, which means that self-regulation has a positive and insignificant effect on the academic achievement of part-time worker students at FKIP ULM. For the hard work character variable, the p-value is 0.000 < 0.05 and the t-statistic value is 6.608> 1.96 with an original sample value of 0.67, which means that hard work character has a positive and significant effect on the academic achievement of part-time working students at FKIP ULM. The results of the simultaneous test with r-square in this study obtained a coefficient of determination of 0.475, which means that 47.5% of academic achievement is determined by self-regulation and hard work character and the remaining 52.5% is influenced by other variables outside this study.